Moral Purpose, Political Action, and Liberalism: An Attempt at a Philosophical and Political Inquiry - Biro, Peter L. (My University, 1985)
This thesis represents an attempt at a philosophical inquiry into the nature of political action and its place in liberal theory.
I begin by considering whether action must be explained teleologically and whether non-purposive accounts of behaviour can be generally adequate. In finding that purposive behaviour fundamentally characterizes action, I question the assumption in liberal political theory, beginning with Hobbes, that mechanistic laws of behaviour can provide man with a science of politics.
Hobbes , represents for me, the first stage in the revolt against teleological politics. I consider the important contributions that Immanuel Kant and finally John Rawls make to the liberalism of anti-telelogical politics.
I then consider the liberal critique of Hobbes' portrait of man. This is represented by Jean-Jacques Rousseau. Rousseau's critique is undermined by his failure to reject market politics.
Finally, I consider the market-model of society, which is seen to be the ultimate embodiment of mechanistic, anti-teleological politics.
Keywords: Political Science; Political Science